Preiotarea în limba română - Klimkowski, Tomasz (Wydawnictwo Naukowe UAM, 2014)
This paper analyses the phenomenon of preiotacisation in Romanian, which consists in the prothesis of a semi-consonant [j] before the initial [e]. In fact, this is only an orthographic convention, because in most cases (eu, ele, ești, e, este, eram) the initial [je] segment is a proper diphthong of different origins that is written e, instead of ie, like in other words. Preiotacisation appears only in the pronouns el, ei and in the Old Romanian pronunciation of some borrowed words. The [j]-prothesis cannot be separated from other types of prothesis attested in the spoken language. This tendency is parallel to the similar phenomenon from Slavic languages and possibly was developed under their influence.
Preiotacisation in Romanian
Keywords: pronunciation; preiotacisation; prothesis; Romanian